2011
DOI: 10.1007/s11172-011-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanocomposite platinum catalysts on porous silicon

Abstract: Platinum nanoparticles supported on porous silicon were synthesized by radiation chemi cal reduction in solutions of reverse micelles. The Pt nanoparticles obtained are electron deficient. The degree of porosity, conductivity type, pore geometry of the silicon matrix, and precursor parameters affect the size, shape, and charge state of the platinum catalysts.Platinum and platinum based composites are consid ered to be the best catalysts of oxygen reduction reactions (ORR) and hydrogen oxidation reactions (HOR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A recent report by Liu et al [ 7 ] also showed that the Ag nanoparticles supported on PS chips exert high catalytic reduction on p-nitrophenol. Meanwhile, Yashtulov et al [ 8 ] studied the influence of PS’s porosity and conductivity type on the phase/charge state of Pt in Pt/PS nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report by Liu et al [ 7 ] also showed that the Ag nanoparticles supported on PS chips exert high catalytic reduction on p-nitrophenol. Meanwhile, Yashtulov et al [ 8 ] studied the influence of PS’s porosity and conductivity type on the phase/charge state of Pt in Pt/PS nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a certain self organization of Pd nanoparticles on the PS surface. 3,4,7, 8 The results 3 of the measurements of the integral inten sity of the characteristic bands of plasmon absorption of Pd nanoparticles (λ 1 = 230-265 nm, λ 2 = 290-320 nm), which were obtained during adsorption on the surface of PS of n and p type of conductivity within 72 hours, are listed in Table 4. Later on the integral intensity changed insufficiently.…”
Section: Resultsmentioning
confidence: 99%
“…7, 8 The PS plates were subjected to anode electrochemical etching in water ethanol solution of HF. During the galvanostatic mode of anodizing the current density was within 20-100 mA cm -2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is distinct from the earlier reports of metal/PSi composites obtained from aqueous metal salt solutions using metal hydrides or hydrogen as reducing agents, which result in the formation of much larger metal particles (Coulthard et al, 1993 , 2000 ; Coulthard and Sham, 1998 ). Similarly, the surfactant mediated method using sodium borohydride as reducing agent in aqueous-ethanol solution results in the formation of large metal nanoparticles in the range of 10–50 nm (Yashtulov et al, 2011 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%